Pendekatan Estetika Seni Lukis dalam Pengembangan Desain Gantungan Kunci - Rosdiana Biahimo; Ahmad Iqbal Puluraga; Utina, Fahria; Ferawati S. Nu’u (Politeknik Kebangsaan, 2025)
This study aims to examine the application of the aesthetic approach of painting in the development of key chain designs as creative craft products. The focus of the research lies in how aesthetic principles such as color, line, texture, balance, and visual harmony are implemented through hand-painting techniques to produce designs with high artistic value. The research method used is descriptive qualitative through observation of the design process, visual aesthetic analysis, and documentation of the work. The results show that the painting technique is able to provide a more expressive, detailed, and unique character to the key chain design compared to other decorative methods. The aesthetic approach applied makes the product not only function as an accessory, but also has a stronger artistic value and visual appeal. In addition, the choice of color, composition, and painting style has been proven to influence the user's aesthetic perception and increase the product's selling value. Thus, the application of the aesthetics of painting in key chain design is an effective strategy for producing creative products that are aesthetic, innovative, and competitive in the modern craft industry.